Sphaerocalyptra dermitzakii and Sphaerocalyptra youngii, two new holococcolithophore species from the Aegean Sea (eastern Mediterranean) - Dimiza, M.; Triantaphyllou, M.; Theodoridis, S. (Journal of Nannoplankton Research, 2005)
Living coccolithophores were collected, in August, 2001, from eight stations in the Gulf of Korthi (Andros Island, middle Aegean Sea, eastern Mediterranean), in order to determine the cell density, species composition and biogeographical (spatial and vertical) distribution in this coastal marine ecosystem. The holococcolithophore assemblages in the sampled stations sometimes reached more than 50% of the total standing crop, tending to be dominant especially at the shallower stations. Two new species of Sphaerocalyptra were identified and are described and figured here: Sphaerocalyptra dermitzakii sp. nov. and Sphaerocalyptra youngii sp. nov.